Assembleia Legislativa de Minas Gerais e a sua relação com os parlamentos municipais: análise do Centro de Apoio às Câmaras - Lima, Taíse Leal (2019)
The present study aims to understand the relationship between the Legislative Assembly of Minas Gerais - ALMG - and the municipal parliaments, through the Center of Support to the Chambers - Ceac -. In order to do this, it analyzes the creation, institutionalization and performance of Ceac, in view of the institutional development of the Minas Gerais Assembly and changes in federal relations after the Federal Constitution of 1988. The work carried out qualitative research, exploratory approach with bibliographical research, documentary and case study. It is also pointed out that the case study was guided by official ALMG data and by faceto-face interviews conducted with servers directly linked to Ceac. Ceac is understood as an institutional innovation that stems from the process of institutional change undertaken by the Minas Gerais Assembly, which later led Casa to influence the environment of other organizations. In addition, it is pointed out that the institutionalization of the organ was guided by its technical vocation, aiming to facilitate the relationship of the Mine Assembly with the municipal Councils of the State. Finally, the study made it possible to conclude, in general terms, that Ceac, through its repertoire of action, seeks to contribute to the improvement of municipal legislative activities and constitutes an interface for the input of information from local parliaments. In this way, the Center for the Support of Chambers integrates the overall strategy of the Assembly of Mines in trying to bring the institution closer to the municipal Legislative Houses.